2021
DOI: 10.2147/dhps.s311926
|View full text |Cite
|
Sign up to set email alerts
|

Rational Drug Use Evaluation Based on World Health Organization Core Drug Use Indicators in Ethiopia: A Systematic Review

Abstract: Background: Rational use of medicines plays a vital role in avoiding preventable adverse drug effects, maximizing therapeutic outcomes with promoting patient adherence, and minimizing the cost of drug therapy. Irrational use of drugs is often observed in countries with weak health care systems. No review has been done that systematically expresses rational drug use practice based on the three WHO core drug use indicators in Ethiopia. Thus, this study was aimed to review systematically the prescribing, health-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Percentage of medicines dispensed and percentage of medicines adequately labeled did not meet the WHO rational drug use recommendation. The result was in line with other systematic reviews [ 21 ]. This might result medication error, medicine-related adverse event, and therapeutic failure.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Percentage of medicines dispensed and percentage of medicines adequately labeled did not meet the WHO rational drug use recommendation. The result was in line with other systematic reviews [ 21 ]. This might result medication error, medicine-related adverse event, and therapeutic failure.…”
Section: Discussionsupporting
confidence: 93%
“…This review revealed that only two of the reviewed studies showed complete medicines prescription by generic name. The percentage of generic drug use was ranged from 70.5% to 100% [ 21 ]. The lower level of prescription by generic name was also reported by other systematic reviews and meta-analyses [ 22 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Irrational drug use practices, such as polypharmacy, overuse of antibiotics, and inadequacy of drug labeling, exist all over the globe, predominantly in developing countries. 1 4 Severe irrational drug use has been abundantly evidenced in China. For example, overuse of injections was common, and studies indicated the percentage of injections prescribed per 100 encounters was between 21% and 60%.…”
Section: Introductionmentioning
confidence: 99%